Workplace envy, workplace incivility, and Job satisfaction: an empirical study on nurses.; İşyerİ kiskançliği, İşyerİ nezaketsİzlİğİ ve İş tatmİnİ: hemşİreler üzerİne bİr araştirma - Nida Palabiyik; İbrahim Yikilmaz; Lütfi Sürücü (Uluslararası İktisadi ve İdari İncelemeler Dergisi, 2024)
The aim of this study is to determine the effect of incivility and envy behaviors in the workplace on the job satisfaction of nurses. For this purpose, data were collected from 288 nurses working in a hospital in Erzurum with convenience sampling method. In line with the research model, correlation and multiple regression analysis were performed by means of scales whose validity and reliability were tested. As a result of the analysis, it was determined that workplace incivility and workplace envy had a negative effect on nurses' job satisfaction level. – – Bu çalışmanın amacı; işyerinde nezaketsizlik ve kıskançlık davranışlarının hemşirelerin iş tatmini üzerindeki etkisini belirlemektir. Bu doğrultuda, kolayda örnekleme yöntemiyle Erzurum'daki bir hastanede çalışan 288 hemşireden veri toplanmıştır. Araştırma modeli doğrultusunda, geçerliliği ve güvenirliği test edilen ölçekler vasıtasıyla korelasyon ve çoklu regresyon analizi yapılmıştır. Analizler sonucunda, işyeri nezaketsizliğinin ve işyeri kıskançlığının hemşirelerin iş tatmini üzerinde negatif yönlü bir etkiye sahip olduğu belirlenmiştir.
Keywords: 330; Job Satisfaction; Workplace Envy; Workplace Incivility